Broadband : The Platform of the Digital Economy and a Critical Development Challenge for Morocco - World Bank (World Bank, Washington, DC, 2017)
Morocco strives to reach a similar per capita income level to that of upper-middle income countries, and to reduce unemployment, which particularly affects women and youth. To meet these goals, the government recognizes the need to shift from a low-technology economy with a strong agricultural component to a more diversified economy focused on services and high value-adding industries. As the World Bank World Development Report 2016 highlights, broadband is one of the decisive factors in a nation's competitiveness. Deploying broadband is essential to improve Morocco's international competitiveness and to attract foreign investment. Rolling out broadband is of strategic importance for Morocco, as the country aims to consolidate its promising position in the industrial and manufacturing sectors. This note is organized in three sections:(i) section one provides a summary analysis of recent economic studies that measured the impacts generated by access to and use of ICT and broadband on the economy; (ii) section two analyzes public policies implemented by the Moroccan government since the 1990s, and their impact on the sector; and (iii) section 3 presents the main reforms that the World Bank would recommend that the government carry out in the broadband sector to give itself the means to fulfill its ambitions and finish opening up the broadband sector to competition.